THE ROLE OF COMBINATION OF TEACHING AND RESEARCH IN THE IMPROVEMENT OF EDUCATIONAL COMPONENTS - Goroshko Оlexandra; Drachuk, Vira (SWorld-Ger Conference proceedings, 2023)
According to the main directions of reforming the higher education system according to the requirements of European standards, there is a change in the model of professional training, where scientific activity plays an important role in educational activi